In situ biodeposition measurements on a Modiolus modiolus (horse mussel) reef provide insights into ecosystem services. (5th January 2017) - Kent, Flora E.A.; Last, Kim S.; Harries, Daniel B.; Sanderson, William G.
Abstract: Horse mussel ( Modiolus modiolus ) shellfish reefs are a threatened and declining habitat in the North East Atlantic and support high levels of biodiversity. Shellfish can influence the surrounding water column and modify the quality of material that reaches the seabed by filtering water, actively depositing particles and changing the benthic boundary layer due to surface roughness. In the present study M. modiolus biodeposition was measured in a field location for the first time. The results show that M. modiolus enhance sedimentation and contribute to the downward flux of material to the seabed. Approximately 30% of the total sediment deposition was attributed to active filter feeding and overall, the presence of horse mussels enhanced deposition two fold. The results are discussed in terms of the potential for horse mussel reefs to provide ecosystem services to society, through functions such as benthopelagic coupling and sediment stabilisation. Highlighting the societal benefits supplied by marine habitats can help prioritise conservation efforts and feed into the sustainable management of coastal water bodies.